PERANAN AUDIT MANAJEMEN DALAM MENILAI EFEKTIVITAS DAN EFISIENSI PELAYANAN TERHADAP PASIEN DI DEPARTEMEN BEDAH RUMKITAL DR. RAMELAN SURABAYA - Yunita, Ayu Puspa; Bayangkara, I.B.K. (Universitas 17 Agustus 1945 Surabaya, 2020)
ABSTRACT,This study aims to determine,the role of, management audits in assessing the effectiveness and, efficiency of service to patients in the surgical, departement Rumkital Dr. Ramelan Surabaya. This research is a case study with qualitative, descriptive method, throught interview, observation and questionnaire. The effectiveness and, efficiency, of,services to patients is analyzed and,evaluated by comparing the, criteria, causes, effects and providing recommendations. Based on the result of, the research, it can be conclude that the activity or service activity, in Departement of Surgery has been run efficiently but not yet effective because the, waiting time of elective surgery of spine surgery patient not yet in accordane with predefined, time standard.